Ask Question
19 October, 18:17

What is the value of h (-2) when h (x) = 3x + 1?

h (-2) =

+3
Answers (1)
  1. 19 October, 19:24
    0
    All you need to do is substitue - 2 into the equation for x,

    h (-2) = 3 (-2) + 1 = - 6 + 1 = - 5
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “What is the value of h (-2) when h (x) = 3x + 1? h (-2) = ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers